EFEKTIVITAS PIJAT OKETANI TERHADAP PRODUKSI ASI: SYSTEMATIC LITERATURE REVIEW - Rizqiya Nur Amalina; Lutfatul Latifah; Mekar Dwi Anggraeni (Indonesian National Nurses Association (INNA) of Central Java, 2022)
Background: Oketani massage is a massage that can increase breast milk output. This study aims to determine the effectiveness of oketani massage on breast milk production. Methods: This study uses a literature review method. The search was limited to articles published from 2017-2021 with quantitative research types. Searches were done on databases such as Google Scholar, Sage, Proquest, Ebsco, and Cochrane, with the keywords oketani massage dan breast milk production. Results: Based on the search results found as many as 58 articles. Then after the screening stage, 9 articles were obtained for review. Based on the review, it was stated that oketani massage can increase the quantity and quality of breast milk production as measured by weighing the baby’s weight, measuring prolactin and oxytocin levels, using IBFAT questionnaire, observation sheet for breast milk production, and assessing the mother’s perception. Conclusion: Oketani massage has effectiveness in increasing breast milk production in postpartum mothers and breastfeeding mothers..